Assessing the relationship between aggression tendencies and the secure parental attachment of children going through early adolescence - Seven, Serdal; Gulay, H.; Damar, M. (My University, 2011)
The purpose of this study is to assess the relationship between aggression tendencies and the sense of security arising from parental relationships of children going through early adolescence. 167 normally developed sixth and seventh grade students participated in the study. In the study, the Intent Attribution Questionnaire and the Parent as a Secure Base Scale were used to gather data. Results of the study illustrated a significantly positive relationship between the children's level of parental attachment and their level of aggression tendencies. Another outcome from the study was that the level of secure parental attachment had a significant predictive effect on the level of aggression tendencies. While a secure attachment bond with the mother portrayed a significant predictive effect on the level of aggression tendencies, a secure attachment bond with the father alone portrayed no predictive effect on the level of aggression tendencies. © IDOSI Publications, 2011.
Keywords: Early adolescence; Parental attachment; Secure attachment; Tendency towards aggression